Supercompactness of spaces of capacities and its consequences - Cherkovskyi, T.M. (Carpathian Mathematical Publications, 2013)
It is proved that the space of normalized real-valued capacities on an openly generated compactum is an absolute retract. Existence of a normal binary subbase for closed subsets in the space of normalized lattice-valued capacities on an openly generated compactum is also shown, which implies that this space is a Dugundji space.